Mountain isolation and the retention of traditional knowledge in the High Atlas of Morocco - Montanari, B.; Irene Teixidor-Toneu (Journal of North African Studies, 2022)
Most literature on Amazigh (Berber) in Morocco and in the Journal of North African Studies revolve around historical, social and political issues. Literature also covers issues of Berber cultural recognition, linguistic identity, and colonization. However, little is known of the ethnobotanical knowledge associated with the traditional way of life that maintains the livelihood and health of Berber communities in isolated regions of the High Atlas. In this paper, we aim to identify whether ethnobotanical knowledge is eroding and whether geographical isolation shapes its transmission in the context of globalization. This paper focuses on the differences between men's and women's medicinal plant knowledge. We conducted ethnographic and ethnobotanical fieldwork over 33 months interviewing 51 men and 146 women in ten villages with different degrees of access to urban areas and modern commodities and services. We used and analyzed quantitative data drawn from plants’ free listing to assess whether ethnobotanical knowledge is eroding. Our results show that gendered differences in ethnobotanical knowledge are concomitant of integration to market economies, revealing significant knowledge retention differences in the most isolated study sites. We conclude that despite strong forces at work to integrate remote communities into globalized markets, there are important risks to TEK which supports local environmental and community health.